Penerapan Pendekatan Arsitektur Ekologis Pada Resort dan Villa di Kuta Mandalika, Lombok - Aryasaputra, Made Agus; Trimarianto, Ciptadi; Wiryawan, I Wayan (Jurnal Arsitektur Universitas Udayana; Vol 9 No 02 (2021): Jurnal Arsitektur, Universitas UdayanaDO - 10.24843/jaunud.v9i02.71975, 2021)
Tourism accommodation facilities are developing very quickly in areas that have certain tourist attractions, especially the Kuta Mandalika area. Resort facilities are in great demand in this area because they provide lodging, recreation, relaxation, and sports facilities. The development of tourism accommodation facilities sometimes puts pressure on the environment, due to the large consumption of electricity and the lack of waste management. To minimize this, the application of an ecological architectural approach needs to be done. The aim is to produce a resort villa design that can reduce the negative environmental impact of resort operations and attract visitors. The method used in compiling this research is a qualitative method of collecting observational data from studies of similar objects to several tourism accommodation facilities. The data collection was also carried out by studying literature on the ecological architectural approach. The results of the research obtained are the application of ecological architecture to resort villas can be applied by increasing water catchment areas, structuring vegetation, using environmentally friendly materials, cross ventilation, applying renewable energy and waste management. Keyword: ecological, environmentally friendly, resort villa, tourism accommodation facilities